Psicose e toxicomanias: um estudo psicanalítico - Soares, Alenuska Nadja Rego de Queiroz (2012)
This paper is a case study that aims to discuss the effects of drug abuse by a person with psychotic structure from a psychoanalytical perspective. The interest in this subject was born from an internship experience in the Mental Health area in which a psychotic patient had a drug abuse problem and the service treating him had difficulties dealing with this. In order to accomplish the objective of this work four theoretical chapters were written and the case is discussed throughout them articulating the theoretical issues with clinical practice. A literature review revealed that Freud and Lacan did not dedicate themselves to the study of the effect of drug use by psychotic patients but they made important contributions unfolding the theoretical and clinical psychoanalytical practice. Contemporary psychoanalytic authors suggest that the drug use made by psychotics differs from the use by neurotics, because of the particularity of the psychotic structure. It was found that drug use in psychosis can operate in three different ways: the first refers to drug use as substitute of a missing signifier helping the psychotic patient building a social bond. The second function is to intensify psychotic phenomena and the third function is to operate as an attempt to diminish those same phenomena. We conclude that, while the use of drugs in neurosis provides an individualist way of satisfaction, that excludes social aspects. For psychosis such use may operate differently and may play a role in social integration, among others effects. Such discussion can help move forward the direction of treatment of psychosis when the case involves drug use